Substrate preference of protein kinase B isoforms can vary depending on the cell line. - Miguel S Palma; Samantha R Perez; Aida Husain; Deepali Bhandari (PLoS ONE)
Many proteins in higher eukaryotes, especially those with crucial functions, have multiple isoforms with redundant roles providing protection against potential functional deficiencies in one isoform. However, these isoforms can also have some unique roles. Protein kinase B, also known as Akt, is one such protein that has three isoforms encoded on different genes. Due to high sequence similarity and the general lack of specific reagents, most studies on Akt generalize their findings and do not distinguish between the isoforms. Using an established chemical genetic strategy and a set of known Akt substrates, this work explores substrate specificity of Akt isoforms under steady state conditions in two commonly used cell lines. This strategy can be applied to study any Akt isoform-specific substrates of interest in any cell line of choice as long as the cell line can be transfected.